Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
The equation x
The equation x 2
The equation x 2 +xy+xz+yz can be factorised as follows:
The equation x 2 +xy+xz+yz can be factorised as follows:x
The equation x 2 +xy+xz+yz can be factorised as follows:x 2
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x 2
The equation x 2 +xy+xz+yz can be factorised as follows:x 2 +xy+xz+yz=(x 2 +xy)+(xz+yz)=x(x+y)+z(x+y)=(x+z)(x+y)Hence, x 2 +xy+xz+yz=(x+z)(x+y)
Answer:
= (y-1) (xy-z)
Step-by-step explanation:
First we expand them -
= xy^2 - xy - yz - z
= xy(y-1)-z(y-1)
= (y-1) (xy-z)
Hope this helped
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.